Cannabigerol Prevents Quorum Sensing and Biofilm Formation of Vibrio harveyi - Aqawi, Muna; Gallily, Ruth; Sionov, Ronit Vogt; Zaks, Batya; Friedman, Michael; Steinberg, Doron (Frontiers in Microbiology, 2020)
Cannabigerol (CBG) is a non-psychoactive cannabinoid naturally presented in trace amounts in the Cannabis plant. So far, CBG has been shown to exert diverse activities in eukaryotes. However, much less is known about its effects on prokaryotes. In this study, we investigated the potential role of CBG as an anti-biofilm agent and anti-quorum sensing against V. harveyi. Quorum sensing (QS) is a cell-to-cell communication between bacteria that involves small signaling molecules called autoinducers, enabling bacteria to sense the surroundings. The autoinducers cause alterations in gene expression and induce the production of virulence factors such as bioluminescence, pigment production, motility and biofilm formation. The effect of CBG was tested on V. harveyi grown under planktonic and biofilm conditions. CBG reduced the QS-regulated bioluminescence and biofilm formation of V. harveyi at concentrations not affecting the bacterial growth. CBG also reduced the motility of V. harveyi in a dose-dependent manner. We further observed that CBG increased LuxO expression and activity, with a concomitant 80% downregulation of the LuxR gene. Exogenous addition of autoinducers could not overcome the QS-inhibitory effect of CBG, suggesting that CBG interferes with the transmission of the autoinducer signals. In conclusion, our study shows that CBG is a potential anti-biofilm agent via inhibition of the QS cascade.